2023
DOI: 10.1002/jac5.1887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extended pharmacist involvement in discharge transitions of care on hospital readmission rates: Prospective, randomized, parallel arm design trial

Natalie Tasseff,
Sandra Axtell,
Bianca Nixon

Abstract: Pharmacist involvement in transitions of care has been shown to improve patient outcomes and reduce readmission rates. Pharmacists reduce medication errors at discharge by ensuring all home medications continued are appropriate, provide pharmacist discharge patient medication education on new and existing medications therapies, and evaluate the safety and efficacy of the patient's medication therapy in order to decrease readmission rates. Results from this study may provide a financial benefit for hospital rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Tasseff et al 2 used an internally-validated readmission risk tool to identify patients included in their TOC programs. Our systematic review 3 also showed significant heterogeneity in the methods used to identify and provide services for these patients.…”
mentioning
confidence: 99%
“…Tasseff et al 2 used an internally-validated readmission risk tool to identify patients included in their TOC programs. Our systematic review 3 also showed significant heterogeneity in the methods used to identify and provide services for these patients.…”
mentioning
confidence: 99%